Status quo of China hydrogen strategy in the field of transportation and international comparisons. (18th August 2021) - Meng, Xiangyu; Gu, Alun; Wu, Xinguo; Zhou, Lingling; Zhou, Jian; Liu, Bin; Mao, Zongqiang
Abstract: This paper discusses the current development strategy, technology and industrialization of China's hydrogen energy industry in the transportation field, summarizes the characteristics and development experience, and makes a comparative study with the situation of some developed countries. The results show that the current development of hydrogen energy has formed a broad consensus in China and is becoming the overall development of China's national level consciousness. However, China's hydrogen energy industry is still facing problems such as high cost of comprehensive utilization, imperfect standards and regulations for hydrogen energy utilization, obvious tendency of industrial blind development and structural overcapacity risk. Therefore, some policy suggestions were proposed for the future development, such as strengthening top-level design, strengthening pilot demonstration, promoting the development of the whole hydrogen industry chain, and reducing the cost of hydrogen and fuel cell vehicles in the field of transportation. Graphical abstract: Image 1 Highlights: The development of hydrogen energy industry has become China's national consensus. China has formed three major industrial clusters of hydrogen and fuel cells. China's hydrogen industry is facing the risk of overcapacity. China should strengthen the top-level design of hydrogen development strategy.